Effects of transdermal dosage forms on IN VITRO pig skin permeation of glucosamine hydrochloride - Punlapa Anusitthakul (Chulalongkorn University, 2014)
Thesis (M.Sc. in Pharm)--Chulalongkorn University, 2007